Influence of Material Used for the Regenerator on the Properties of a Thermoacoustic Heat Pump - KRUK, Bartłomiej (Archives of Acoustics, 2013)
Research in termoacoustics began with the observation of the heat transfer between gas and solids.Using this interaction the intense sound wave could be applied to create engines and heat pumps. The mostimportant part of thermoacoustic devices is a regenerator, where press of conversion of sound energy intothermal or vice versa takes place. In a heat pump the acoustic wave produces the temperature differenceat the two ends of the regenerator. The aim of the paper is to find the influence of the material used forthe construction of a regenerator on the properties of a thermoacoustic heat pump. Modern technologiesallow us to create new materials with physical properties necessary to increase the temperature gradienton the heat exchangers. The aim of this paper is to create a regenerator which strongly improves theefficiency of the heat pump.